العنف المدرسي من وجهة نظر طلاب السنة أولى ثانوي - شربي, بشير (جامعة الوادي - University of Eloued, 2022)
هدفت هذه الدراسة الى التعرف على مستوى العنف المدرسي داخل المؤسسات التربوية من وجهة نظر طلاب السنة أولى ثانوي بثانوية توفيق المدني بمدينة ورقلة وكذا الفروق الموجودة في هذا المستوى بإختلاف الجنس والتخصص، أستخدم المنهج الوصفي التحليلي، وقد تم اختيار العينة عن طريق الحصر الشامل ب (300) طالب وطالبة خلال السنة الدراسية ( 2019/2020 )، استعملت أداة الإستبانة لجمع البيانات ممثلة في مقياس السلوك العدواني ال رشود" مكون من 65 بند بعد إعادة التأكد من خصائصه السيكومترية على عينة قوامها (30) طالب وطالبة التي أكدت صلاحيته للإستخدام، أظهرت النتائج على أن مستوى العنف المدرسي منخفض لدى طلاب السنة اولى ثانوي بثانوية توفيق المدني بمدينة ورقلة ، وعدم وجود فروق في مستوى العنف المدرسي باختلاف الجنس والتخصص لدى طلاب السنة اولى ثانوي بثانوية توفيق المدني بمدينة ورقلة. This study aimed to identify the level of school violence within educational institutions from the point of view of students of the first year of secondary school in Tawfiq al-Madani secondary school in the city of Ouargla, as well as the differences in this level according to the difference of gender and specialization. (Male and female students) During the academic year (2019/2020), she used the questionnaire tool to collect data represented in the Rushed Aggressive Behavior Scale consisting of 65 items after re-verifying its psychometric properties on a sample of (30) male and female students who confirmed its suitability for use, the results showed However, the level of school violence is low among students in the first year of secondary school in Tawfiq al-Madani secondary school in Ouargla, and there are no differences in the level of school violence according to gender and specialization among students of the first year of secondary school in Tawfiq al-Madani secondary school in Ouargla.
دراسة ميدانية بثانوية توفيق المدني بمدينة ورقلة
مقال
Keywords: العنف ، العنف المدرسي ، طلاب السنة اولى ثانوي; violence, school violence, first year high school students